Comparative genomics of the primary endosymbiont Buchnera aphidicola in aphid hosts and their coevolutionary relationships - Yukang Liang; Rebecca B. Dikow; Xu Su; Jun Wen; Zhumei Ren (BMC Biology, 2024)
Abstract Background Coevolution between modern aphids and their primary obligate, bacterial endosymbiont, Buchnera aphidicola, has been previously reported at different classification levels based on molecular phylogenetic analyses. However, the Buchnera genome remains poorly understood within the Rhus gall aphids. Results We assembled the complete genome of the endosymbiont Buchnera in 16 aphid samples, representing 13 species in all six genera of Rhus gall aphids by shotgun genome skimming method. We compared the newly assembled genomes with those from GenBank to comprehensively investigate patterns of coevolution between the bacteria Buchnera and their aphid hosts. Buchnera genomes were mostly collinear, and the pan-genome contained 684 genes, in which the core genome contained 256 genes with some lineages having large numbers of tandem gene duplications. There has been substantial gene-loss in each Buchnera lineage. We also reconstructed the phylogeny for Buchnera and their host aphids, respectively, using 72 complete genomes of Buchnera, along with the complete mitochondrial genomes and three nuclear genes of 31 corresponding host aphid accessions. The cophylogenetic test demonstrated significant coevolution between these two partner groups at individual, species, generic, and tribal levels. Conclusions Buchnera exhibits very high levels of genomic sequence divergence but relative stability in gene order. The relationship between the symbionts Buchnera and its aphid hosts shows a significant coevolutionary pattern and supports complexity of the obligate symbiotic relationship.